Gallurgical Enrichment of Silvinite Mines and Technology of Potassium Ore Processing - Khaydarova Munira Davronovna; Shaymanova Rano Soatmurodovna; Muhammadiyev Husayn Alizoda (International Journal on Integrated Education, 2022)
The article discusses the issues of studying the processing of sylvinite ore, the development of effective technological systems for halurgical enrichment and the analysis of the main stages of processing sylvinite, identifying prospects for accelerating the processing of potash ore and developing recommendations.